Hubungan antara Penerimaan Diri dengan Fear of Missing Out (FoMO) pada Mahasiswa Generasi Z Pengguna Aplikasi TikTok di Sumatera Barat - Sakinatun Hasanah; Yolivia Irna Aviani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to analyze the relationship between self-acceptance and fear of missing out (FoMO) among Generation Z students who use the TikTok application in West Sumatra. A quantitative approach was employed with 386 Generation Z students selected through purposive sampling. The self-acceptance variable was measured using an instrument developed by the researchers based on Bernard’s (2013) theory, while the FoMO variable used a scale adapted into Indonesian by Kurniawan and Utami (2022) based on Sette et al. (2020). Data were analyzed using correlation techniques. The findings reveal a significant negative correlation between self-acceptance and FoMO (r = –0.522; p = 0.000 < 0.05). This indicates that the higher the level of self-acceptance, the lower the level of FoMO experienced by Generation Z students using TikTok. Conversely, lower self-acceptance is associated with higher levels of FoMO. These results support the notion that low self-acceptance may trigger negative social comparison on social media, increased anxiety, and dependence on external validation. This study offers practical implications for students, parents, and higher education institutions to pay closer attention to self-acceptance as a preventive factor against the negative effects of excessive social media use.